Measuring the Influence of Humor Towards ad Recall in Undergraduate Students of Institute Technology Bandung - Nurdiansyah, Raedi; Iskandar, Budi Permadi (Journal of Business and Management, 2013)
Advertising is an important component in business activity. One way to see the effectiveness of advertising can be viewed from ad recall. This research measure the influence of humor in creating ad recall and how much humor affects. Utilize undergraduate students of ITB population as a sample research, data collection conducted using interview method about recall and the reason that recalling the ad. Based on humor as a one of a part of execution of the ad, the research findings are factors that influence undergraduate students of ITB in recalling the ad. Humor got a positive result. Purpose: The goal of this thesis is to measure the role of humor in influencing ad recall. By knowing what drives college student of ITB recalling the advertising, humor can be measured. Design/methodology/approach: Utilize undergraduate students of ITB as a sample, with simple random sampling the data gathered using interview about recall and the reason that recalling the ad based on creative advertising framework. Findings: The research findings are factors that influence undergraduate students of ITB in recalling the ad. Humor got a positive result although it is not the highest. The factor that most make students of ITB recalling the ad is endorser factor. Besides, music and tagline is also quite influential. Research limitations/implications: This thesis focuses only toward male and female current enrolled undergraduate students of ITB, Bandung. Practical implications (if applicable): The outcome of this thesis is a consideration to the person, group, agencies, or companies to make advertisement, especially college students as it is target market. Originality/value: This research measured humor toward ad recall based on humor as one of a part of execution and creative advertising framework.Â Keywords: Advertising, Recall, Humor, Execution.Category: Marketing, Advertising.----------------------------------DISCLAMER: This paper is created by undergraduate students of School of Business and Management ITB in partial fulfillment of the requirement of the degree Bachelor of Management. Journal of Business and Management is not responsible for the content, opinions, or any other materials expressed here.